2007
DOI: 10.1021/jf071205v
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of Hydroxycinnamic Acid Glucosides and Evaluation of Their Ability To Stabilize Natural Colors via Anthocyanin Copigmentation

Abstract: This work describes the chemical synthesis of O-aryl-beta-D-glucosides and 1-O-beta-D-glucosyl esters of hydroxycinnamic acids. In particular, O-aryl-beta-D-glucosides were efficiently prepared via a simple diastereoselective glycosylation procedure using phase transfer conditions. Despite the lability of its ester linkage, 1-O-beta-D-caffeoylglucose could also be obtained using a Lewis acid catalyzed glycosylation step and a set of protective groups that can be removed under neutral conditions. Hydroxycinnami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 30 publications
5
61
0
Order By: Relevance
“…Balakshin et al (2011) reported that phenyl glycosidestype LC linkages are present via carbohydrate signals C1-H1 around δ C / δ H 104 -99/4.8 -5.2 ppm according to model compound data of Terashima et al (1996) . The data of phenylpropanoid glucosides also support this expectation (Galland et al 2007 ;Mazur et al 2007 ). The correlations are observed at δ C / δ H 98.6/4.97 and 102.3/4.99 ppm in the spectrum of XL-F2, whereas the correlations are observed at δ C / δ H 99.5/5.11 and 102.3/4.77 ppm in the spectrum of LCC-AcOH.…”
Section: Carbohydrate Anomeric Regionsmentioning
confidence: 54%
“…Balakshin et al (2011) reported that phenyl glycosidestype LC linkages are present via carbohydrate signals C1-H1 around δ C / δ H 104 -99/4.8 -5.2 ppm according to model compound data of Terashima et al (1996) . The data of phenylpropanoid glucosides also support this expectation (Galland et al 2007 ;Mazur et al 2007 ). The correlations are observed at δ C / δ H 98.6/4.97 and 102.3/4.99 ppm in the spectrum of XL-F2, whereas the correlations are observed at δ C / δ H 99.5/5.11 and 102.3/4.77 ppm in the spectrum of LCC-AcOH.…”
Section: Carbohydrate Anomeric Regionsmentioning
confidence: 54%
“…Indeed, at pH 3.5, the flavylium ion of malvin (pK h =1.52 ( 0.02) (65) represents no more than ca. 1% of the total pigment concentration.…”
Section: Resultsmentioning
confidence: 99%
“…4-β- D -glucopyranosylcoumaric acid: p- coumaric acid glucoside and ferulic acid glucoside were chemically synthesized according to Galland et al 59 and references therein.…”
Section: Methodsmentioning
confidence: 99%